Guapira siqueirae (Nyctaginaceae, Pisonieae), a new species from Espírito Santo State, Brazil - Sandoli Rossetto, Elson Felipe; Ferraz, José Roberto (Phytotaxa, 2020)
Guapira siqueirae is described in the present paper as a new species from the Atlantic Forest of Espírito Santo State (SE-Brazil). This species can be morphologically distinguished from the other Guapira species by the distal portion of the branches, the bases of the petioles and peduncle that are ferruginous-puberulous, the inflorescences with alternate or opposite branches, the lustrous adaxial surface of matures leaves, and the larger anthocarps. A distribution map and comparisons with morphologically related species are also provided.